ABT-737 reverses the acquired radioresistance of breast cancer cells by targeting Bcl-2 and Bcl-xL - Li Ji-Yu (Journal of Experimental & Clinical Cancer Research, 2012)
Abstract Background Acquired radioresistance of cancer cells remains a fundamental barrier to attaining the maximal efficacy of radiotherapy for the treatment of breast cancer. Anti-apoptotic proteins, such as Bcl-2 and Bcl-xL, play an important role in the radioresistance of cancer cells. In the present study, we aimed to determine if ABT-737, a BH3-only mimic, could reverse the acquired radioresistance of the breast cancer cell line MDA-MB-231R by targeting Bcl-2 and Bcl-xL. Methods The radiosensitivity of MDA-MB-231 and MDA-MB-231R cells was compared using colony formation assays. Reverse-transcription PCR and western blot were performed to detect the expression of Bcl-2 and Bcl-xL in the cancer cell lines. Annexin V flow cytometric analysis and caspase-3 colorimetric assay were used to evaluate apoptosis of the cancer cells. Cell viability was measured using the Cell Counting Kit-8. The animals used in this study were 4 to 6-week-old athymic female BALB/c nu/nu mice. Results The MDA-MB-231R cells were more radioresistant than the MDA-MB-231 cells, and Bcl-2 and Bcl-xL were overexpressed in the MDA-MB-231R cells. While ABT-737 was able to restore the radiosensitivity of the MDA-MB-231R cells in vitro and in vivo experiment, it was not able to enhance the radiosensitivity of the MDA-MB-231 cells. In addition, ABT-737 increased radiation-induced apoptosis in the MDA-MB-231R cells. Bcl-2 and Bcl-xL were down regulated in the MDA-MB-231R cells following treatment with ABT-737. Conclusions Targeting of the anti-apoptotic proteins Bcl-2 and Bcl-xL with ABT-737 may reverse the acquired radioresistance of MDA-MB-231R cells in vitro and in vivo. These findings suggest an attractive strategy for overcoming the acquired radioresistance of breast cancer cells.